PENERAPAN PBL BERBASIS INTERAKTIF WORD WALL UNTUK MENINGKATKAN MOTIVASI DAN MINAT HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 5 SDN 32 GRESIK - Moch. Efinnudin Zukhri; Khoirul Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to evaluate the effectiveness of the wordwall-based Problem Based Learning (PBL) learning model in increasing students' interest in learning outcomes and motivation to learn Indonesian language material. The research background shows that student learning outcomes have not yet reached expectations due to a lack of active participation and learning motivation. Motivation to learn is very important to increase interest in learning outcomes. The research method used was a mixed method with a one-group pretest-posttest design. The research subjects were 26 grade 5 students at UPT SDN 32 Gresik, consisting of 10 boys and 16 girls. Research instruments include pretest-posttest tests, observations, and interviews. Data analysis was carried out descriptively qualitatively and quantitatively. The research results showed a significant increase in students' interest in learning outcomes and learning motivation. The posttest results show that the average interest in student learning outcomes increased to 73% and learning motivation to 73.5%, both of which are good criteria. Thus, the wordwall-based PBL model is effective in increasing students' interest in learning outcomes and learning motivation.